79.9k views
5 votes
2x-5y=6y=3x+4solving systems using substitution

User Astreal
by
5.0k points

1 Answer

6 votes

System


\begin{gathered} 2x-5y=6 \\ y=3x+4 \end{gathered}

Let's substitute Equation 2 into Equation 1 and solve for x


\begin{gathered} 2x-5(3x+4)=6 \\ 2x-5\cdot3x-5\cdot4=6 \\ 2x-15x-20=6 \\ -13x=6+20 \\ -13x=26 \\ x=(26)/(-13) \\ x=-2 \\ \end{gathered}

Now, solve for y


\begin{gathered} y=3x+4 \\ y=3\cdot(-2)+4 \\ y=-6+4 \\ y=-2 \\ \end{gathered}

The solution to the system is x = -2 and y = -2.

User Gluck
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.